BeiDou 3 signal quality analysis and its impact on users. Issue 4 (5th September 2019) - Thoelert, Steffen; Antreich, Felix; Enneking, Christoph; Meurer, Michael
Abstract: This work presents signal analysis results based on observations of the new BeiDou 3 signals, which appeared in the years 2017 to 2019. After a brief introduction of the measurement facility, the basic analysis of the quality of the signals in spectral and modulation domains is introduced. This covers the transition from BeiDou 2 up to BeiDou 3 including the test and validation phase at the beginning of BeiDou 3. On the basis of captured in‐phase (I) and quadrature (Q) samples, a detailed overview of the BeiDou 3 satellite payload characteristics including signal deformation analysis is provided. This work also assesses how such imperfections will influence the pseudorange measurements and consequently provide the capability for an error analysis for safety‐critical applications. Considering the measured power in relation to the boresight angle of the satellite, a cut through the antenna pattern of different satellites is presented, and the antenna symmetry properties are assessed.